2020
DOI: 10.1152/ajpheart.00649.2019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of resistance vessel function in human skeletal muscle: guidelines for experimental design, Doppler ultrasound, and pharmacology

Abstract: The introduction of duplex Doppler ultrasound almost half a century ago signified a revolutionary advance in the ability to assess limb blood flow in humans. It is now widely used to assess blood flow under a variety of experimental conditions to study skeletal muscle resistance vessel function. Despite its pervasive adoption, there is substantial variability between studies in relation to experimental protocols, procedures for data analysis, and interpretation of findings. This guideline results from a colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 305 publications
(380 reference statements)
1
44
0
1
Order By: Relevance
“…The results of this inquiry yielded two major findings. First, in agreement with current thought (Limberg et al, 2020;Thijssen, Black, et al, 2011), the assessments of conduit artery function (FMD and its derivatives) and resistance artery function (derivatives of RH, PLM, and ROV) appear to reflect two different aspects of vascular function, with the indices derived from the RH, PLM, and ROV being strongly correlated with each other, but not with FMD and its derivatives. The second major finding of this study is that leg vascular function, especially resistance artery function, is strongly related to VȮ 2 max, accounting for approximately 30% of the variance in VȮ 2 max not accounted for by known influencers, like body mass, sex, and BMI.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The results of this inquiry yielded two major findings. First, in agreement with current thought (Limberg et al, 2020;Thijssen, Black, et al, 2011), the assessments of conduit artery function (FMD and its derivatives) and resistance artery function (derivatives of RH, PLM, and ROV) appear to reflect two different aspects of vascular function, with the indices derived from the RH, PLM, and ROV being strongly correlated with each other, but not with FMD and its derivatives. The second major finding of this study is that leg vascular function, especially resistance artery function, is strongly related to VȮ 2 max, accounting for approximately 30% of the variance in VȮ 2 max not accounted for by known influencers, like body mass, sex, and BMI.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, in the current study vascular function was measured in multiple ways (FMD, RH, PLM, and ROV) on a group of young, healthy adults. As illustrated in Figure 1 and further described in Table 1, lower limb vascular function assessed by the resistance artery tests RH, PLM, and ROV exhibits strong relationships with each other (r = 0.54-0.83, p < .05), supporting the notion that they reflect some of the same physiological processes (Limberg et al, 2020). This comes in agreement with data from Rossman, Groot, Garten, Witman, & Richardson (2016) and Walker et al (2016) who observed significant correlations between PLM-induced hyperemia and RH in various populations.…”
Section: Are the Various Indices Of Vascular Function Interchangablmentioning
confidence: 52%
See 3 more Smart Citations